Wooden foreign body in the orbitocranial location - Erol, FS; Topsakal, C; Ozveren, MF; Ozturk, M; Kaplan, M; Yilmaz, T (Swets Zeitlinger Publishers, 2002)
Orbitocranial injuries caused by a wooden foreign body are rarely encountered. We present a 17-year-old boy who sustained an intracerebral injury from a wooden foreign body via the transorbital route. Almost all neuro-oplithalmological signs were present due to penetration of the material into the optic canal and superior orbital fissure. There was a minute laceration on the upper eyelid, whereas the eye bulb was macroscopically intact. The wooden foreign body (6-5 cm in length) was removed via the upper eyelid. The diagnostic and therapeutic modalities of intracranial injuries caused by a wooden foreign body through the transorbital route are discussed in this paper.
Keywords: optic canal; orbitocranial penetrating injury; superior orbital fissure; wooden foreign body